Health‐related quality‐of‐life results from PALETTE: A randomized, double‐blind, phase 3 trial of pazopanib versus placebo in patients with soft tissue sarcoma whose disease has progressed during or after prior chemotherapy—a European Organization for research and treatment of cancer soft tissue and bone sarcoma group global network study (EORTC 62072). Issue 17 (29th May 2015) - Coens, Corneel; van der Graaf, Winette T. A.; Blay, Jean‐Yves; Chawla, Sant P.; Judson, Ian; Sanfilippo, Roberta; Manson, Stephanie C.; Hodge, Rachel A.; Marreaud, Sandrine; Prins, Judith B.; Lugowska, Iwona; Litière, Saskia; et al.
Abstract : BACKGROUND: Health‐related quality of life (HRQoL) was an exploratory endpoint in the PALETTE trial, a global, double‐blind, randomized, phase 3 trial of pazopanib 800 mg versus placebo as second‐line or later treatment for patients with advanced soft tissue sarcoma (N = 369). In that trial, progression‐free survival was significantly improved in the pazopanib arm (median, 4.6 vs 1.6 months; hazard ratio, 0.31; P  < .001), and toxicity of pazopanib consisted mainly of fatigue, diarrhea, nausea, weight loss, and hypertension. METHODS: HRQoL was assessed using the 30‐item core European Organization for the Research and Treatment of Cancer (EORTC) Quality‐of‐Life Questionnaire (EORTC QLQ‐C30) at baseline and at weeks 4, 8, and 12 in patients who received treatment on protocol. The primary HRQoL endpoint was the EORTC QLQ‐C30 global health status scale. RESULTS: Compliance with HRQoL assessments was good, ranging from 94% at baseline to 81% at week 12. Differences in scores on the EORTC QLQ‐C30 global health status subscale between the 2 treatment arms were not statistically significant and did not exceed the predetermined, minimal clinically important difference of 10 points ( P  = .291; maximum difference, 3.8 points). Among the other subscales, the pazopanib arm reported significantly worse symptom scores for diarrhea ( P  < .001) loss of appetite ( P  < .001), nausea/vomiting ( P  < .001), and fatigue ( P  = .012). In general, HRQoL scores tended to decline over time in both arms. CONCLUSIONS: HRQoL did not improve with the receipt of pazopanib. However, the observed improvement in progression‐free survival without impairment of HRQoL was considered a meaningful result. The toxicity profile of pazopanib was reflected in the patients' self‐reported symptoms but did not translate into significantly worse overall global health status during treatment. Cancer 2015;121:2933–2941. © 2015 American Cancer Society . Abstract : Although health‐related quality of life is not improved by pazopanib, improved progression‐free survival without impairment of health‐related quality of life can be considered a meaningful result in patients with pretreated, metastatic soft tissue sarcoma. The toxicity profile of pazopanib is reflected in the patients' self‐reported symptoms but does not translate into significantly worse overall global health during treatment, because patients maintain role and social functioning.